Analgesic Effect of Duloxetine on an Animal Model of Monosodium Iodoacetate‐Induced Hip Osteoarthritis. Issue 2 (2nd October 2019) - Kawarai, Yuya; Orita, Sumihisa; Nakamura, Junichi; Miyamoto, Shuichi; Suzuki, Miyako; Inage, Kazuhide; Hagiwara, Shigeo; Suzuki, Takane; Nakajima, Takayuki; Akazawa, Tsutomu; Ohtori, Seiji
ABSTRACT: We investigated the efficacy of duloxetine on hyperalgesia, histopathological and radiographic findings, pain‐related sensory innervation of dorsal‐root ganglia (DRG), and spinal changes in a rat model of induced hip osteoarthritis (OA). The right hip joints of male Sprague–Dawley rats ( n = 6 rats/group) in the Sham group were injected with 25 μl of sterile saline and 25 μl of sterile saline with 2 mg of monosodium iodoacetate (MIA) were injected to the MIA + Vehicle and MIA + Duloxetine groups. We injected duloxetine 20 mg/kg intraperitoneally in the MIA + Duloxetine group 28 days after injection, whereas rats in the MIA + Vehicle group were injected with 0.5 ml of 20% dimethyl sulfoxide. We assessed hyperalgesia, histopathological changes, immunoreactive (‐ir) neurons for calcitonin gene‐related peptide and activating transcription factor 3 in DRG, and immunoreactive neurons for ionized‐calcium‐binding adaptor molecule 1 (Iba1) in the dorsal horn of the spinal cord. MIA administration into the hip joint let to mechanical hyperalgesia of the ipsilateral hind paw ( p < 0.05). A single injection of duloxetine significantly attenuated it in induced hip OA ( p < 0.05) and suppressed the number of Iba1‐ir microglia of the ipsilateral dorsal horn ( p < 0.05). These results suggest that a single injection of duloxetine suppressed mechanical hyperalgesia and may influence the expression of Iba1 in the microglia of the ipsilateral dorsal horn in the MIA‐induced hip OA. This finding implies the inhibitory effects of duloxetine against neuropathic pain, which may lead to a change of microglial activities. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:422‐430, 2020